Respuesta :
Answer:
The length will be 5 feet, width will be 4 feet.
Step-by-step explanation:
Given:
volume of the box = 40 ft^3
Length of the box = (2x-1)ft
Width of the box = (3x-5)ft
Height of the box = 2ft,
To Find:
The length and width of the box = ?
Solution:
We know that,
[tex]\text{volume of the box} = Length \times breadth \times height[/tex]
[tex]40= (2x-1) \times (3x-5) \times 2[/tex]
[tex]40 = (2x-1) \times(6x-10)[/tex]
[tex]40 = 12x^2 - 20x - 6x +10[/tex]
[tex]40 = 12x^2 - 26x +10[/tex]
[tex]12x^2 - 26x +10-40 = 0[/tex]
[tex]12x^2 -26x -30 = 0[/tex]-----------------------(1)
Solving eq(1) by quadratic equation formula
[tex]x = \frac{-b \pm \sqrt{b^2-4ac}}{2a}[/tex]
Substituting the values
[tex]x = \frac{-(-26) \pm \sqrt{(-26)^2-4(12)(-30)}}{2(12)}[/tex]
[tex]x = \frac{26 \pm \sqrt{676 -4(-360)}}{24}[/tex]
[tex]x = \frac{26 \pm \sqrt{2116}}{24}[/tex]
[tex]x = \frac{26 \pm 46}{24}[/tex]
[tex]x = \frac{26 + 46}{24}[/tex] [tex]x = \frac{26-46}{24}[/tex]
[tex]x =\frac{72}{24}[/tex] [tex]x = \frac{-20}{24}[/tex]
x = 3 x =-0.833
Neglecting the negative value,
we have x = 3
Then the length will be
(2(3)-1) = (6-1) =5 ft
The Width will be
(3(3)-5) = (9-5) = 4 ft